183k views
5 votes
Factor the expression shown below completely. 18x^2 -60x +50

2 Answers

1 vote
For this case we have the following polynomial:

18x ^ 2 -60x +50
We do common factor 2:

2 (9x ^ 2 -30x + 25)
We now factor the expression into parentheses.
We have then:

2 (3x-5) (3x-5)
Then, rewriting we have:

2 (3x-5) ^ 2
Answer:
The factored expression is:

2 (3x-5) ^ 2
User Alexandre Ribeiro
by
5.8k points
5 votes
18x² - 60x + 50
= 2 (9x² - 30x + 25 ) ⇒⇒⇒ take 2 as common from all terms
note: 9x² = 3x * 3x and 25 = 5*5 and 3x * 5 *2 = 30x

so, this is a complete square

= 2(3x-5)(3x-5)
= 2(3x-5)²
User Behnam Hedayat
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.